2008
DOI: 10.1080/10627190802602509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Classroom Assessment Practices on Students' Achievement Goals

Abstract: This study examined the effects of classroom assessment practices on students' achievement goals. The study included 1,636 ninth grade students and 83 science teachers from Muscat public schools in Oman. Results from hierarchical linear modeling techniques showed that class contextual features and teachers' teaching experiences and assessment practices interacted significantly with students' characteristics in influencing students' achievement goals. Recommendations, implications, and suggestions for practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 27 publications
3
35
0
1
Order By: Relevance
“…The finding of the study was in agreement with that of Alkharusi [45], who studied the effects of classroom assessment practices on students' achievement goals.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…The finding of the study was in agreement with that of Alkharusi [45], who studied the effects of classroom assessment practices on students' achievement goals.…”
supporting
confidence: 80%
“…This finding is not in line with Zimbicki's [46] finding that motivation level and self-efficacy reached high levels when students were engaged in alternative assessment. Also, Alkharusi [45] reported a different finding supporting a move towards the use of more alternative assessment. The results of his study suggested that learners' self-efficacy on performance-approach goal within a classroom was dependent jointly on class gender, teaching experiences, and frequent use of alternative assessments.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, performance-oriented assessment perceptions are created among students by assessment environments where assessment-related tasks are difficult, exam grades are prioritized over learning, students' performance is prioritized over their effort, and social comparisons are taken as the criteria for success (Alkharusi, 2010). Students' levels of learning-and performance-oriented assessment perceptions affect their beliefs about their self-efficacy, their achievement goal orientations, and their academic performances (Alkharusi, 2008;Brookhart, Walsh & Zientarski, 2006). For instance, while higher performance-oriented perceptions lead to lower beliefs of self-efficacy, higher learning-oriented perceptions lead to higher beliefs of self-efficacy (Alkharusi, 2009).…”
Section: Academic Burnoutmentioning
confidence: 99%
“…Problems around methodology are not only regarding how to transfer knowledge directly but also how to lead the students to do self-learning and seek information (Abi Aad, 2011;Alkharusi, 2008). Therefore, an appropriate method will provide motivation for the students to continue their learning process.…”
Section: Introductionmentioning
confidence: 99%